Enhanced glycolysis-derived lactate promotes microglial activation in Parkinson’s disease via histone lactylation - Qixiong Qin; Danlei Wang; Yi Qu; Jiangting Li; Ke An; Zhijuan Mao; Jingyi Li; Yongjie Xiong; Zhe Min; Zheng Xue (npj Parkinson's Disease)
Abstract The switch from oxidative phosphorylation to glycolysis is crucial for microglial activation. Recent studies highlight that histone lactylation promotes macrophage homeostatic gene expression via transcriptional regulation, but its role in microglia activation in Parkinson’s disease (PD) remains unclear. Here, we demonstrated that inhibiting glycolysis with 2-deoxy-d-glucose alleviates microgliosis, neuroinflammation and dopaminergic neurons damage by reducing lactate accumulation in PD mice. Notably, we observed a marked increase in histone lactylation, particularly H3K9 lactylation, in microglia in the substantia nigra of PD mice. Mechanistically, CUT&Tag and Chip-qPCR analyses revealed that H3K9 lactylation enriched at the SLC7A11promoter and activated its expression. Importantly, inhibiting SLC7A11 by sulfasalazine mitigated microglia-mediated neuroinflammation and improved motor function in PD mice. Moreover, we found that lactate-induce histone lactylation is dependent on P300/CBP. Collectively, our findings demonstrate that glycolysis-derived lactate promotes microglial activation via histone lactylation and provide a potential therapeutic strategy for PD.